2021
DOI: 10.1017/ice.2021.381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the costing methodology of published studies estimating costs of surgical site infections: A systematic review

Abstract: Objectives: Surgical site infections (SSIs) are associated with increased length of hospitalization and costs. Epidemiologists and infection control practitioners, who are in charge of implementing infection control measures, have to assess the quality and relevance of the published SSI cost estimates before using them to support their decisions. In this review, we aimed to determine the distribution and trend of analytical methodologies used to estimate cost of SSIs, to evaluate the quality of costing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 113 publications
0
5
0
Order By: Relevance
“…SSIs are an ever-increasing phenomenon worldwide due to different factors and are responsible for generating important costs [ 51 , 52 ]. This cost depends on many factors, including the patient himself and the type of surgery [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…SSIs are an ever-increasing phenomenon worldwide due to different factors and are responsible for generating important costs [ 51 , 52 ]. This cost depends on many factors, including the patient himself and the type of surgery [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…28 All studies evaluated in a systematic review reported some economic benefit associated with SSI prevention, but there is significant heterogeneity in the literature related to cost accounting. 29,30 In the United States, SSIs are believed to account for $3.5 billion to $10 billion annually in healthcare expenditures. 31,32 Finally, data reported to the CDC NHSN show that SSIs can be caused by antibiotic-resistant bacteria such as methicillin-resistant Staphylococcus aureus , vancomycin-resistant Enterococci, and multidrug-resistant gram-negative bacilli.…”
Section: Section 1: Rationale and Statements Of Concernmentioning
confidence: 99%
“…28 All studies evaluated in a systematic review reported some economic benefit associated with SSI prevention, but there is significant heterogeneity in the literature related to cost accounting. 29,30 In the United States, SSIs are believed to account for $3.5 billion to $10 billion annually in healthcare expenditures. 31,32…”
Section: Section 1: Rationale and Statements Of Concernmentioning
confidence: 99%
“…As soon as our consensus document will be implemented by the Italian Scientific Societies, it will be interesting to analyze its clinical and economic impact in our geographical context. However, our recommendations could be generalized also in low- and middle-income countries where it has been recently highlighted the impact of simple, cost-effective, sustainable, and adaptable strategies on the reduction of SSIs morbidity risk and the associated costs [ 130 , 131 , 132 ].…”
Section: Discussionmentioning
confidence: 99%